TYPES OF MORAL VALUES IN “RALPH BREAK THE INTERNET WRECK IT RALPH 2”: TYPES OF MORAL VALUES IN “RALPH BREAK THE INTERNET WRECK IT RALPH 2” - Suarjana, Imade (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2023)
This study aims to determine the types of moral values and the context of the situation when conveyed the types of moral values expressed in the film “Ralph Breaks the Internet: Wreck It Ralph 2”. Moral values were discussed based on the theory of Moral Values proposed by Audi (2007) and the context situation based on the theory proposed by Halliday & Hasan (1985). In collecting the data, the first step was to watched the film and marked the utterances that contain moral values in each scene and film dialogue. The data analyzed was conducted by used qualitative method. Qualitative method was a type of social science research that collects and works with non-numerical data and that seeks to interpret meaning from these data that help us understand social life through the study of targeted populations or places. In analyzed the data, there were some steps in order to solved the problem of the study. First discussion there was an analyzed of moral values and then the second was an analyzed of the context of the situation such as field, tenor, and mode so that the data analyzed was more accurate. Next, nine types of moral values were discussed in the film “Ralph Breaks the Internet: Wreck-It Ralph 2. The study classified the data based on moral values and then analyzed the context of the situation. In terms of moral values, there were nine types of moral values expressed, namely Bravery 1, Self Confidence 3, Respect 3, Love and Affection 1, Kind and Friendly 2, Optimism 3, Never Give Up 2, Peace Ability 1 the total is 16 data including the meaning with the context of situation that consists of the field, tenor and mode. Meanwhile, the type of moral values of Strong Belief was not found in this film because in the context of Strong Belief, meant was one's relationship with God or religion. While in the movie "Ralph Breaks the Internet: Wreck It Ralph 2" told about how Character in a virtual video game or avatar game solves the problem and does not find any religious element at all. In the film "Ralph Breaks the Internet: Wreck It Ralph 2", the type the most dominant moral values ​​found are Self Confidence, Optimism, and Respect because, in this film, their mission was to succeed in improving the Vanellope game.